Integrated Statistical and Automatic Process Control : Hybrid Process and Quality Control. - Venkatesan, G. (Alpha Science International, 2014)
This text book on INTEGRATED STATISTICAL AND AUTOMATIC PROCESS CONTROL covers mathematical process and stochastic modeling, algorithm development, simulation principles, analysis of simulation results to develop process regulation schemes for cost effective and efficient process control and statistical control procedures for producing quality products. Manufacturing processes, in order to provide good quality products that satisfy the needs of customers at affordable cost, need to be controlled during process operations. Different types of processes require different types of control that may b.